Development of Indonesian Organic Agrifood: Certification Process and Issues - Walaela, Khais; Suprehatin, Suprehatin; Adhi, Andriyono Kilat (Agro Bali : Agricultural Journal, 2025)
The global growth of organic agrifood has also reached Indonesia, creating opportunities and challenges for smallholder farmers. This study aims to explore the certification process and identify key barriers to obtaining organic certification for Indonesian agricultural products. Using a qualitative case study approach, data were collected through in-depth interviews with three certified organic farming groups in Central Java—each producing rice, vegetables, or coffee. Data analysis was conducted using descriptive methods and graphical tools such as spider charts. The findings reveal that both pre-certification and certification stages typically require three months, not including land conversion, which may be shortened if prior organic practices are recognized. Major challenges during these stages include business planning, seed availability, group coordination, investment capital, pest management, and contamination prevention. These issues are rooted in limited knowledge and technical skills regarding organic standards and practices. Technological interventions—such as the use of ozone plasma, Internet of Things (IoT), and mobile cold storage—were found to support compliance and productivity, particularly in vegetable farming. However, constraints such as land fatigue, lack of rotation, limited access to organic inputs, and high certification costs persist. The study suggests that improved training, mentoring, institutional support, and access to organic inputs are essential to overcoming certification barriers and strengthening farmers’ participation in organic value chains. These insights offer practical implications for policymakers and stakeholders to promote sustainable organic farming in Indonesia.